Differential effects of omeprazole and pantoprazole on the pharmacodynamics and pharmacokinetics of clopidogrel in healthy subjects: randomized, placebo-controlled, crossover comparison studies - Angiolillo, D J; Gibson, C M; Cheng, S; Ollier, C; Nicolas, O; Bergougnan, L; Perrin, L; LaCreta, F P; Hurbin, F; Dubar, M (Clinical pharmacology and therapeutics, 2011)
Four randomized, placebo-controlled, crossover studies were conducted among 282 healthy subjects to investigate whether an interaction exists between clopidogrel (300-mg loading dose/75-mg/day maintenance dose) and the proton-pump inhibitor (PPI) omeprazole (80 mg) when they are administered simultaneously (study 1); whether the interaction, if any, can be mitigated by administering clopidogrel and omeprazole 12 h apart (study 2) or by increasing clopidogrel to 600-mg loading/150-mg/day maintenance dosing (study 3); and whether the interaction applies equally to the PPI pantoprazole (80 mg) (study 4). Relative to levels after administration of clopidogrel alone in studies 1,2,3, and 4, coadministration of PPI decreased the AUC(0-24) of the clopidogrel active metabolite H4 by 40, 47, 41, and 14% (P ≤ 0.002), respectively; increased maximal platelet aggregation (MPA) induced by 5 micromol/l adenosine diphosphate (ADP) by 8.0, 5.6, 8.1, and 4.3% (P ≤ 0.014), respectively; and increased the vasodilator-stimulated phosphoprotein phosphorylation-platelet reactivity index (VASP-PRI) by 20.7, 27.1, 19.0 (P < 0.0001), and 3.9% (P = 0.3319), respectively. The results suggest that a metabolic drug-drug interaction exists between clopidogrel and omeprazole but not between clopidogrel and pantoprazole.